Customer Loyalty Through Word of Mouth, Service Quality and Customer Satisfaction as Intervening Variables - Dwi Gemina; Palahudin; roby, Robyansyah (Jurnal Manajemen, 2026)
Management must maximize marketing techniques in Bogor Regency’s cutthroat hotel industry by enhancing service quality and utilizing word-of-mouth (WOM) to foster client loyalty and satisfaction. According to field statistics, the Jayakarta Mountain Resort Cisarua Bogor has less than ideal occupancy rates and poor levels of patron satisfaction and loyalty. The relationship between WOM, service quality, and customer loyalty is examined in this study, along with the function of customer satisfaction as an intervening variable. The study used purposive sampling to survey 150 participants using a quantitative, descriptive-verificative design. Using SPSS version 25, data were examined using path analysis and the Sobel test. The findings show that customer happiness, which in turn boosts customer loyalty, is positively and significantly impacted by word-of-mouth and service quality. Through satisfaction, both factors have a direct and indirect impact on loyalty. According to the coefficient of determination, WOM, service quality, and customer happiness account for 86.6% of the variation in customer loyalty. Customer satisfaction is a key mediating factor, according to the Sobel test. These results demonstrate that building loyalty in the resort sector requires improving service quality and encouraging favorable word-of- mouth. To foster long-term consumer loyalty, management is encouraged to implement customer-driven promotional initiatives, enhance service responsiveness, and fortify loyalty programs. In the end, customer happiness is the primary factor that increases the influence of word-of-mouth and service quality on loyalty, highlighting its crucial function in guaranteeing competitive advantage.